Detection of Early Murine Colorectal Cancer by MMP-2/-9–Guided Fluorescence Endoscopy. Issue 1 (January 2016) - Schwegmann, Katrin; Bettenworth, Dominik; Hermann, Sven; Faust, Andreas; Poremba, Christopher; Foell, Dirk; Schäfers, Michael; Domagk, Dirk; Lenz, Philipp
Abstract : Background: Patients with ulcerative colitis are at increased risk for colorectal cancer and endoscopic surveillance is mandatory. Matrix metalloproteinases (MMPs)-2 and -9 activities are increased in malignant colonic mucosa. The aim of the study was to evaluate molecular imaging of MMP-2/-9 by fluorescence endoscopy (FE) for early tumor detection. Methods: Colorectal cancer in mice (n = 28) was induced by azoxymethane and dextran sodium sulfate. Twenty-four hours after intravenous injection of a nonpeptidic, Cy5.5-labeled MMP-selective tracer, tumor development was assessed in vivo by white light endoscopy and FE. Topical administration of the tracer was also investigated (after 5 minutes and 24 hours). Colonic tumors were evaluated ex vivo by fluorescence reflectance imaging, immunohistochemistry, Western blot analysis, and zymography. Results: Imaging of MMP-2/-9 expression by FE achieved a significantly higher contrast of the fluorescence signal in colonic adenomas compared with the adjacent nonmalignant mucosa ( P < 0.001). Fluorescence reflectance imaging detected a significantly higher tracer uptake in adenoma compared with healthy mucosa ( P < 0.001) and revealed a tumor size–dependent increase of tracer uptake ( P < 0.01). Topical tracer administration did not facilitate tumor detection. Immunohistochemistry, Western blot analysis, and zymography indicated higher levels of MMP-2 and -9 in high-grade dysplasia and pT1 tumors ex vivo. Conclusions: MMP-2/-9 expression was significantly increased in colorectal neoplasia. FE allows direct visualization of a prognostic parameter (here MMP-2/-9) on a molecular level and may improve the characterization of colorectal lesions and the adenoma detection rate in the future. Abstract : Article first published online 8 October 2015.Supplemental Digital Content is Available in the Text.